Rancang Bangun Aplikasi Penentuan Lokasi Agen Baru Pada CV. Air Putih - Arief, Ferdian; Hartati, Sulis Janu; Sudarmaningtyas, Pantjawati (Jurnal JSIKA, 2014)
Abstract: The problem in this research is how to determine a good/fit new agent. To determining the fit area using Gravity Location Model ( GLM ) model to get the point of the fit area and use Analytical Hierarchy Process ( AHP ) model to get ranked best candidate agent . This should consider several variables such as distance, volume of demand , cost and distance of the two areas is less than 5 km. After obtained a suitable area to be opened next agent then takes variables such as the price and capacity of each customers warehouse in a radius of 500 meters to be modeled. If GLM result is no customers on radius fit, then the application will take three customers that have the shortest distance to the point . After getting the prospective agent by area fit, the AHP calculation is performed which results will be sorted decline so we would get the best ranking candidate agent . The purpose of this research is to build an application that is able to model the data to the GLM model and AHP to generate new good/fit candidate agents. The results showed that using pieces of GLM model and AHP is able to provide the best alternative agent in accordance with the companys business objectives . The results of this study show that : the first condition of the application was able to retrieve all customer data within fit radius when fit point falls in the region with the coordinates contained -3.585538052, 114.7174578 . Second conditionÂ is when the fit radius have no customer, then the application will take 3 the closest customers on coordinate radius -3.60041056, 114.7055044. AHP calculation process will be done when the results of the GLM calculations have been done . Prospective new agent based GLM condition 1 , obtained id 84023 customers with the best value 31 % , id 84 026 customers with the best value 21%, customer id 84025 with the best value 20%. While the new candidate agents based GLM condition 2 , obtained id 84 031 customers with the best value 35 % , id 84046 with the best value 33% and customer id 84034 with the best value 32%. Keywords: Agent, Distribution, Gravity Location Model, Analytical Hierarchy Process.